2011 International Joint Conference on Biometrics (IJCB) 2011
DOI: 10.1109/ijcb.2011.6117547
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition across time lapse: On learning feature subspaces

Abstract: There is a growing interest in understanding the impact of aging on face recognition performance, as well as designing recognition algorithms that are mostly invariant to temporal changes. While some success has been made on this front, a fundamental questions has yet to be answered: do face recognition systems that compensate for the effects of aging compromise recognition performance for faces that have not undergone any aging? The studies in this paper help confirm that age invariant systems do seem to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
(31 reference statements)
2
24
0
Order By: Relevance
“…Furl et als [16] and O'Toole et als [17] conducted studies to investigate the impact of cross training and matching on White and Asian races. Similar training biases were investigated by Klare and Jain [18], who showed that aging-invariant face recognition algorithms suffer from decreased performance in non-aging scenarios.…”
Section: Prior Studies and Related Workmentioning
confidence: 88%
“…Furl et als [16] and O'Toole et als [17] conducted studies to investigate the impact of cross training and matching on White and Asian races. Similar training biases were investigated by Klare and Jain [18], who showed that aging-invariant face recognition algorithms suffer from decreased performance in non-aging scenarios.…”
Section: Prior Studies and Related Workmentioning
confidence: 88%
“…This observation suggests learning an age gap specific model for robust face recognition [10,16]. However, other demographic factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters used for both the alignment and the MLBP descriptors have been optimized in a number of previous studies by our research group. Our prior research has relied on such holistic representations, and these parameters represent our best practices [49]. It is also important to note that we are not able to improve the accuracy of this holistic representation by increasing the size (or IPD) of the face image.…”
Section: Resultsmentioning
confidence: 99%
“…While they outperform the nose and mouth, they only do marginally better. However, in cognitive science and automated face recognition literature, the eyes and/or eyebrows have generally been regarded as the most useful component for recognition, while the nose and mouth are regarded as being less informative [18], [22], [29], [49].…”
Section: ) Component Representations -Pcso Databasementioning
confidence: 99%